Improving HIV Surveillance Data by Using the ATra Black Box System to Assist Regional Deduplication Activities. (1st September 2019) - Ocampo, Joanne Michelle F.; Hamp, Auntré; Rhodes, Anne; Smart, J. C.; Pemmaraju, Raghu; Poschman, Karalee; Hess, Kristen L.; Bhattacharjee, Reshma; Flynn, Colin; Anderson, Bridget J.; Dowling, James E.; Maccormack, Fred; et al.
Abstract : Background: Focused attention on Data to Care underlines the importance of high-quality HIV surveillance data. This study identified the number of total duplicate and exact duplicate HIV case records in 9 separate Enhanced HIV/AIDS Reporting System (eHARS) databases reported by 8 jurisdictions and compared this approach to traditional Routine Interstate Duplicate Review resolution. Methods: This study used the ATra Black Box System and 6 eHARS variables for matching case records across jurisdictions: last name, first name, date of birth, sex assigned at birth (birth sex), social security number, and race/ethnicity, plus 4 system-calculated values (first name Soundex, last name Soundex, partial date of birth, and partial social security number). Results: In approximately 11 hours, this study matched 290, 482 cases from 799, 326 uploaded records, including 55, 460 exact case pairs. Top case pair overlaps were between NYC and NYS (51%), DC and MD (10%), and FL and NYC (6%), followed closely by FL and NYS (4%), FL and NC (3%), DC and VA (3%), and MD and VA (3%). Jurisdictions estimated that they realized a combined 135 labor hours in time efficiency by using this approach compared with manual methods previously used for interstate duplication resolution. Discussion: This approach discovered exact matches that were not previously identified. It also decreased time spent resolving duplicated case records across jurisdictions while improving accuracy and completeness of HIV surveillance data in support of public health program policies. Future uses of this approach should consider standardized protocols for postprocessing eHARS data.